William Medill papers - Medill, William, 1802-1865.
Correspondence, account books, and other papers documenting Medill's service as first assistant postmaster general (1845), commissioner of Indian affairs (1845-1850), and first comptroller of the U.S. treasury (1857-1861). Topics include local Ohio politics; railroad politics; President James K. Polk's settlment of the Oregon question; dissatisfaction of Ohio Democrats with the administrations of presidents Polk, Pierce, and Buchanan; abolitionism; and the Mexican War. Correspondents include William Allen, Luther Day, Augustus C. Dodge, James John Faran, Richard M. Johnson, John Y. Mason, Samuel Medary, Allen Granbery Thurman, David Tod, and Clement L. Vallandigham.
Microfilm edition of selected correspondence available
Microfilm of copies in the Manuscript Division.
In part, photocopies.
Library of Congress Geography and Map Division.
Lawyer, U.S. representative and governor of Ohio, and U.S. government official.
Collection material in English.
Keywords: Allen, William, -- 1803-1879 -- Correspondence; Buchanan, James, -- 1791-1868.; Day, Luther, -- 1813-1885 -- Correspondence; Dodge, Augustus C. -- 1812-1883 -- Correspondence; Faran, James John, -- 1808-1892 -- Correspondence; Johnson, Richard M. -- 1780-1850 -- Correspondence; Mason, John Y. -- 1799-1859 -- Correspondence; Medary, S. -- 1801-1864 -- Correspondence; Pierce, Franklin, -- 1804-1869.; Polk, James K. -- 1795-1849.; Thurman, Allen Granbery, -- 1813-1895 -- Correspondence; Tod, David, -- 1805-1868 -- Correspondence; Vallandigham, Clement L. -- 1820-1871 -- Correspondence; Democratic Party (Ohio); United States. -- Bureau of Indian Affairs; United States. -- Department of the Treasury; United States. -- Post Office Department; Antislavery movements; Indians of North America -- Government relations; Mexican War, 1846-1848.; Oregon question; Railroads -- Political aspects -- United States; Ohio -- Politics and government -- 1787-1865.; Oregon -- Boundaries; United States -- Politics and government -- 1845-1861.; Governors -- Ohio; Lawyers; Public officials; Representatives, U.S. Congress -- Ohio